2013
DOI: 10.1364/ao.52.004343
|View full text |Cite
|
Sign up to set email alerts
|

Image encryption using polarized light encoding and amplitude and phase truncation in the Fresnel domain

Abstract: In this paper, an image encryption scheme based on polarized light encoding and a phase-truncation approach in the Fresnel transform domain is proposed. The phase-truncated data obtained by an asymmetric cryptosystem is encrypted and decrypted by using the concept of the Stokes-Mueller formalism. Image encryption based on polarization of light using Stokes-Mueller formalism has the main advantage over Jones vector formalism that it manipulates only intensity information, which is measurable. Thus any intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…This encryption technique leads to enhanced immunity against known-plaintext attacks. The use of polarized light was also suggested as an efficient encryption method to increase the image quality and edge detection of objects embedded in various media [6,7]. Interestingly, other references have focused on encryption procedures to color images based on Arnold [8], and gyrator [9,10] transforms.…”
Section: Introductionmentioning
confidence: 99%
“…This encryption technique leads to enhanced immunity against known-plaintext attacks. The use of polarized light was also suggested as an efficient encryption method to increase the image quality and edge detection of objects embedded in various media [6,7]. Interestingly, other references have focused on encryption procedures to color images based on Arnold [8], and gyrator [9,10] transforms.…”
Section: Introductionmentioning
confidence: 99%
“…This is done by setting two random phase masks in the input and the Fourier planes. Since the publication of this method, the DRPE scheme has been applied in different domains, such as fractional Fourier transform (FRT) 9,10 , Fresnel transform (FrT) 11,12,13 , gyrator transform (GT) 14,15 , quaternion Fourier transform 16 , diffractive imaging 17 , dual fractional Fourier-wavelet 18 , fractional Mellin 19 , and Hartley transform 20 . Nevertheless, it has been demonstrated that DRPE scheme is vulnerable to some type of attacks 21,22,23 and due to its high shift sensitivity, it requires high alignment accuracy in the spatial domain systems.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [33] watermarked three gray-scale images into the three channels of a color image using neighbor pixel value subtraction and addition algorithm. Apart from watermarking, many algorithms and infrastructures such as color-image encryption techniques [34,35], polarization [36,37], photon counting imaging [38], and coherent diffractive imaging [39][40][41] have been further developed in order to enhance the security of any cryptosystem.…”
Section: Introductionmentioning
confidence: 99%